THU0629 TREATMENT PATTERNS WITH DISEASE MODIFYING ANTI-RHEUMATIC DRUGS IN UNITED STATES VETERANS WITH NEWLY DIAGNOSED RHEUMATOID ARTHRITIS, PSORIATIC ARTHRITIS, OR ANKYLOSING SPONDYLITIS. (June 2019) - Walsh, Jessica A.; Pei, Shaobo; Penmetsa, Gopi; Sauer, Brian; Patil, Vikas; Walker, Jodi; Clewell, Jerry; Douglas, Kevin; Clegg, Daniel; Cannon, Grant; Halwani, Ahmad
Abstract : Background: Delays in treatment for inflammatory arthritis (IA) are associated with unfavorable outcomes, including impaired quality of life, irreversible joint damage, and disability. Objectives: To characterize treatment initiation patterns in patients with newly diagnosed rheumatoid arthritis (RA), psoriatic arthritis (PsA), and ankylosing spondylitis (AS). Methods: Incident IA cases were identified between January 1, 2007 and December 31, 2015, in patients enrolled in the Veteran Health Administration, using International Classification of Diseases codes and natural language processing. Patterns of treatment initiation and non-treatment with disease modifying anti-rheumatic drugs (DMARDs) were assessed in the 12-month follow-up period after the incident diagnosis. Results: The population consisted of 12, 118 IA patients (9, 711 RA, 1, 472 PsA, 935 AS), with 91.3% males and a mean age of 63.7. In total, 58.2% of patients initiated a DMARD within 12 months after diagnosis (RA 60.0%, PsA 64.3%, AS 29.6%) (Figure). A DMARD was dispensed ≤30 days after IA diagnosis in 41.2% of patients and ≤90 days in 50.0% of patients. Rheumatology specialty care was accessed during the study period, prior to DMARD dispensation, by 82.7% of patients exposed to a non-biologic DMARD and 90.0% of patients exposed to a biologic DMARD. The percentage of IA patients with DMARD exposure during the 12-month follow-up period increased from 48.8% in 2008 to 66.4% in 2015. Conclusion: Approximately one-half of patients received treatment with a DMARD within 90 days after their initial IA diagnosis. DMARD treatment rates during the initial 12 months after diagnosis increased between 2007 and 2015, but non-treatment remained common, particularly in patients with AS. Timely access to a rheumatology provider is likely important for early DMARD treatment. References: [1] Ng, et al. BMJ Open. 3:e002468. Disclosure of Interests: Jessica A. Walsh Grant/research support from: Abbvie, Pfizer, Consultant for: Abbvie, Celgene, Lilly, Novartis, Shaobo Pei: None declared, Gopi Penmetsa: None declared, Brian Sauer Grant/research support from: Amgen, Vikas Patil: None declared, Jodi Walker Shareholder of: Abbvie, Employee of: Abbvie, Jerry Clewell Shareholder of: Abbvie, Employee of: Abbvie, Kevin Douglas Shareholder of: Abbvie, Employee of: Abbvie, Daniel Clegg Grant/research support from: Amgen grant, Grant Cannon Grant/research support from: Amgen Inc., Ahmad Halwani Grant/research support from: Bristol-Myers Squibb, Kyowa Hakko Kirin, Roche, Abbvie, Genentech, Immune Design, miRagen, Amgen, Seattle Genetics, Takeda, Pharmacyclics